Prevalence of knee injury among football players in Dharan, a sub-metropolitan city in eastern Nepal - Pokharel, Bishnu; Acharya, Ajeet; Thakur, Dhiraj; Sharma, Sushil; Shah, Amit Bikram (Journal of Gandaki Medical College-Nepal, 2025)
Introduction: Most injuries in football occur to the lower extremities. The knee possesses the highest risk. Knee injuries in football are of great concern because they result in substantial physical disability, financial cost, lost playing hours, and may even end a career. Most football clubs in Nepal do not have their own football ground. Players have to practice on the field or public grounds, which are poorly maintained. Nepali football players are thus at higher risk for injuries. This study aimed to determine the prevalence of knee injury among professional football players of the Dharan sub-metropolitan city, Nepal. Methods: A cross-sectional study was conducted in five wards of Dharan, randomly selected from 20 wards. All the players in the wards were enrolled in the study. It was a face-to-face interview based on a questionnaire followed by a knee examination performed by an Orthopaedic surgeon between March 2021 to May 2021. The Tegner-Lysholm Score was used to assess the current status of the participant’s knee. Results: A total of 93 players participated in the study. The most common age group was 16 to 25 years. The mean BMI of the players was 22.4±3.4 kg/m², 8.6% of players were underweight, 16.1% were overweight, and 4.3% were obese. Twenty-nine (39%) participants had a knee injury. The mean Tegner-Lysolm Score of the participants with injured knees was 89±12. Only 13.7% had consulted health professionals after the injury and received some treatment. Conclusions: There was a high prevalence of knee injury among football players.